Kwestia płci w prawie unijnym - Cieśliński, Aleksander (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The idea of this paper is to evaluate all the leading aspects of women and their sex that are relevant in EU system. In order to do this what is analyzed first is genesis of current status of these issues and long evolution from solely economic perspective to social and even political concerns. The role of international legal instruments and primary law provisions is also described. Next, author refers to relations between the theoretical understanding of equality principle as well as the role of sex in society and normative reality. Due to vivid discussions in Poland regarding gender theory and gender mainstreaming special attention was put to these problems and their real meaning for EU law and EU institutions activities. Finally general overview on legal regulations regarding discrimination is presented
Keywords: płeć; równość; dyskryminacja; gender mainstreaming; Unia Europejska